Krig som kulturel velsignelse eller forbandelse? - Første verdenskrig i en nationalkonservativ dansk optik - Bendtsen, Bjarne Søndergaard (Slagmark - Tidsskrift for idéhistorie, 2018)
Although Denmark managed to stay neutral throughout World War I, it nevertheless generated a heated debate in the country; most people took a clear stand for one side or the other. After the traumatic Danish defeat in the 1864 war with Prussia and Austria, Germany was regarded as the arch enemy and not unexpectedly most Danes sided against the Central Powers in the public debate. This was not least the case amongst the national-conservative politicians, intellectuals and artists. They form the focus of my article, and the questions I address are: how did the national-conservatives experience the mental watershed of the war? Was it as a blessing or a curse?